Strategi Akselerasi Pertumbuhan Industri Halal melalui Peran Aktif Perbankan Syariah - I Nyoman, Budiono (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
The Halal Industry is an industry based on Islamic sharia starting from raw materials, management processes to producing products so that the products are halal and good for consumption. The purpose of writing this article is to find out the development of the Halal Industry in Indonesia, the steps taken by the Government in advancing the Halal Industry, and to encourage Islamic Banking to play an active role in accelerating the growth of the Halal Industry. The research methodology used by the author in this article is library research in the form of a literature review in which the overall search results are explained and described in detail and narrative. The results of the study show that the growth of the Halal Industry has increased 2.5 times since being handled by BPJPH, but it needs to continue to be accelerated considering the enormous potential of the Halal Industry. The government has taken steps to accelerate the growth of the Halal Industry, namely by perfecting the provisions for Halal Certification by issuing Law no. 33 of 2014 followed by Government Regulation no. 31 of 2019 was updated with the presence of Law no. 11 of 2020 Concerning Job Creation. The government has also established a Halal Product Assurance Organizing Body (BPJPH) which is tasked with administering Halal Product Assurance. The government also encourages existing institutions to support the growth of the Halal Industry. The strategy for accelerating the growth of the Halal Industry can be carried out by encouraging the Active Role of Islamic Banking in supporting the growth of the Halal Industry through the role of its products. Sharia banking also needs to increase good cooperation with BPJPH, LPH and other institutions in accelerating the body of the Halal Industry in Indonesia.